PENGARUH PENGGUNAAN MEDIA WORDWALL TERHADAP MINAT BELAJAR SISWA DALAM PEMBELAJARAN MATEMATIKA DI KELAS IV SD NEGERI 10 TANJUNG LAGO - Desi Hari Wahyuni; Widya Handayani, Amiruddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Students' interest in learning mathematics is still low due to the implementation of conventional learning models. Lack of use of interactive learning media therefore this study aims to (1) determine the effect of using wordwall media on students' learning interest in learning mathematics in grade IV of STATE ELEMENTARY SCHOOL 10 Tanjung Lago. This study uses the Pre-experimental Design method with a research design of "One group pretest posttest design". The population in this study were all grade IV students of STATE ELEMENTARY SCHOOL 10 Tanjung Lago. The sample of grade IV as an experimental class. Based on the results of the analysis and discussion which show that there is student interest in learning with the use of wordwall media, this is proven by using the t test with t count 17.842 and t table = 2.037 from the results of the paired sample-test on student interest in learning, namely t count > t table. So Ha is accepted and Ho is rejected. It can be concluded that the use of wordwall media has an effect on student interest in learning in mathematics subjects in grade IV of SD Negeri 10 Tanjung